NILAI-NILAI PENDIDIKAN ISLAM YANG TERKANDUNG DALAM TARI RATÉB MEUSEUKAT - Teuku Iskandar (FITRAH: International Islamic Education Journal, 2020)
Ratéb Meuseukat was one of the variety of dance in Aceh that its lyrics and songs contained the messages of Islamic Education, moral values, as well as direction to take a better life. Ratéb Meusekat dance was interesting to be studied further because it not only a folk dance that served as an entertainment tool, but also as a media of Islamic Education. The researcher applied the qualitative approach in this research that was intended to create a description of the presentation form and the messages contained in the Ratéb Meusekat dance. As data collecting method, the researcher did the observation, interview and document recording. In this study the researcher did direct observation about the process of Ratéb Meusekat dance in Lempia studio. The result of this research then indicated that the Ratéb Meusekat dance contained of Islamic Educational messages by means the lesson of faith such as always rember Allah SWT, selawat to our Prophet and the mesage of remembering death. The value of worship like always be grateful. Then moral value such as honor the guest. The last is the value of social relationship that should obeye the instruction and also honor the memory of hero.